Modernism and Metamorphosis: Karin Kiwus' Das Chinesische Examen - James Rolleston (Studies in 20th & 21st Century Literature, 1997)
A Chinese examination requires one to record everything felt or recalled within a given time frame. It "tests" an entire life. Karin Kiwus' poetic tools for taking the exam are monumentality, the freezing of imagined history into the dimension of a statue—that then crumbles back into time; and metamorphosis, the subjection of moments and personae to quasi-musical structures of ceaseless variation.
Keywords: Chinese examination; chinese; record; time frame; feeling; felt; recall; recalled; tests; test; entire life; life; Karin Kiwus; poetry; poetic tool; monumentality; imagined history; freezing; statue; metamorphosis; moments; personae; quasi-musical structures; variation